Application of the distally based sural neurocutaneous flaps in the management of foot and ankle defects in patients with diabetic foot - Dai, Jiezhi; Zhou, Yu; Mei, Shasha; Chen, Hua (Frontiers in Endocrinology, 2022)
Background: We report on our experience with using a distally based sural flaps for soft tissue reconstruction of foot and ankle defects in patients with diabetic foot. Methods: The actual study is a retrospective open, non-controlled, clinical study of 25 patients treated with diabetic foot on whom reconstruction with distally based sural neurocutaneous flaps was performed from May 2019 to Dec 2021. Results: The mean age was 64.9 years, and were 15 male and 10 female. The mean follow-up was 9.8 months, ranged from 6 to 12 months. The size of the flaps ranged from 6×5 to 15×9 cm2. 22 of 25 flaps were survived completely with sufficient blood supply. Two cases had a small superficial necrosis, and resolved following a change of daily dressing and heeled eventually. In one case, partial necrosis was observed that was managed with minor revision and the use of split thickness skin graft. Conclusions: The distally based sural flap is considered to be useful for reconstruction of foot and ankle defects in patients with diabetic foot.